Disentangling the roles of safety climate and safety culture: Multi-level effects on the relationship between supervisor enforcement and safety compliance. (February 2017) - Petitta, Laura; Probst, Tahira M.; Barbaranelli, Claudio; Ghezzi, Valerio
Highlights: The literature on safety culture and safety climate requires greater conceptual clarity and measurement distinctions. A new approach to safety culture is used to assess the unique contributions of culture and climate. Safety climate and culture both uniquely explain the relationship between supervisor enforcement and safety compliance. Understanding of culture and climate is needed to predict safety compliance. Abstract: Despite increasing attention to contextual effects on the relationship between supervisor enforcement and employee safety compliance, no study has yet explored the conjoint influence exerted simultaneously by organizational safety climate and safety culture. The present study seeks to address this literature shortcoming. We first begin by briefly discussing the theoretical distinctions between safety climate and culture and the rationale for examining these together. Next, using survey data collected from 1342 employees in 32 Italian organizations, we found that employee-level supervisor enforcement, organizational-level safety climate, and autocratic, bureaucratic, and technocratic safety culture dimensions all predicted individual-level safety compliance behaviors. However, the cross-level moderating effect of safety climate was bounded by certain safety culture dimensions, such that safety climate moderated the supervisor enforcement-compliance relationship only under the clan-patronage culture dimension. Additionally, the autocratic and bureaucratic culture dimensions attenuated the relationship between supervisor enforcement and compliance. Finally, when testing the effects of technocratic safety culture and cooperative safety culture, neither safety culture nor climate moderated the relationship between supervisor enforcement and safety compliance. The results suggest a complex relationship between organizational safety culture and safety climate, indicating that organizations with particular safety cultures may be more likely to develop more (or less) positive safety climates. Moreover, employee safety compliance is a function of supervisor safety leadership, as well as the safety climate and safety culture dimensions prevalent within the organization.